2007
DOI: 10.1080/08958370601051727
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Ultrafine and Fine Particulate Matter Disrupts Systemic Vascular Function

Abstract: This study investigated the effects of particulate matter (PM) with aerodynamic diameter 0.02-1 μm (noted as PM 1 ) inhalation during exercise on conduit artery and microvascular function. Inhalation of internal combustion-derived PM is associated with cardiovascular mortality and morbidity. Direct action of PM on the vascular endothelium is likely, as a substantial fraction of ultrafine PM translocates from the alveoli to the circulatory system. Sixteen intercollegiate athletes performed 30 min of exercise wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 50 publications
5
93
0
1
Order By: Relevance
“…The near abolishment of FMD was accompanied by a 55% decrease in muscle reoxygenation slope-to-baseline measured by near-infrared spectroscopy (NIRS) after release of artery occlusion and is consistent with compromised reperfusion. This study (19) supported a constrictive response from PM 1 inhalation in the microvasculature that was independent of the observed brachial artery vasoconstriction. Calculation of the return slope of reoxygenation (mMÁs 21 ) to baseline after cuff ischemia (19) provided a rate of decreased reperfusion of the muscle tissue (after 30 minute exercise breathing high PM 1 ) that should be proportional to blood flow.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The near abolishment of FMD was accompanied by a 55% decrease in muscle reoxygenation slope-to-baseline measured by near-infrared spectroscopy (NIRS) after release of artery occlusion and is consistent with compromised reperfusion. This study (19) supported a constrictive response from PM 1 inhalation in the microvasculature that was independent of the observed brachial artery vasoconstriction. Calculation of the return slope of reoxygenation (mMÁs 21 ) to baseline after cuff ischemia (19) provided a rate of decreased reperfusion of the muscle tissue (after 30 minute exercise breathing high PM 1 ) that should be proportional to blood flow.…”
Section: Discussionsupporting
confidence: 69%
“…Instead, these results support a response initiated from the first high (PM 1 ) exposure trial that affected muscle perfusion in the second high (PM 1 ) trial 3 days later. We previously reported diminished flow-mediated vasodilation (FMD) after 30 min of running while breathing high (PM 1 ), suggesting a PM 1 -induced disruption of normal endothelial-mediated vasodilation (19). The near abolishment of FMD was accompanied by a 55% decrease in muscle reoxygenation slope-to-baseline measured by near-infrared spectroscopy (NIRS) after release of artery occlusion and is consistent with compromised reperfusion.…”
Section: Discussionmentioning
confidence: 66%
“…Research into fine and/or ultrafine particulate pollution and exercise has shown both increased genotoxic (Vaclavik-Bräuner et al 2007) and cardiovascular (Rundell et al 2007;Mittleman 2007) risk with increasing aerosol concentrations. During aerobic exercise, inhaled air is taken in predominantly through the mouth, and there is a major increase in minute ventilation and diffusion capacity.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the mechanism involved, particulate matter inhalation has been associated with important alterations of the vascular tone [20,21], the endothelial function [22], the autonomic-nervous system [23], the endogenous fibrinolysis [19] and the systemic inflammation [24], factors that may potentially interact with the arterial wave reflection mechanisms. It could be hypothesized that the effect of PM 10 concentration on the magnitude of the reflection wave could be attributed to a heightened adrenergic-mediated vasoconstriction of the microvascular tree, or to an impaired endothelium-dependent microvascular vaosoconstriction.…”
Section: Discussionmentioning
confidence: 99%